Sosialisasi dan Pelatihan Digitalisasi Administrasi untuk Meningkatkan Efektivitas Kinerja Unit Rekam Medis di RS Bhakti Asih Kota Tangerang - Edi Suyitno; Tyra Septi Diana; Anjani Muslimatun Dawiyah; Nani Tsania Fitri (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Healthcare digitalization administration refers to the use of information technology to automate and improve administrative processes in the provision of health services. This initiative aims to improve efficiency, accuracy, information accessibility, and provide a better experience to patients and healthcare staff. Cloud Computing is a solution that utilizes computer technology and internet-based development, which allows customers to rent and utilize information and communication technology services with the management of infrastructure, platforms and applications carried out by the provider, without any investment on the customer side, thus providing simplicity and efficiency as a whole. Cloud computing is also a transformation and a form of productivity in the future. Cloud computing is the next breakthrough in the era of the internet or virtual communication. The many problems and challenges in public health services in Indonesia, especially in maternal and child hospitals, can actually provide an interesting opportunity to develop an e-health system that can help solve these problems. Some examples of problems are the uneven quantity and quality of health services, the relatively high mortality rate of mothers and babies, various problems in handling tuberculosis patients, and other diseases.